ANALYSIS OF FACTORS AFFECTING ISLAMIC BANK FINANCING FOR THE FISHERIES SECTOR IN INDONESIA - Nur Laili; Hendri Tanjung (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The development of the fisheries sector in Indonesia should get more attention, especially in efforts to increase fishing businesses, limited financial access is still a problem that must be faced by the fisheries sector. Thus, Islamic banking can play a significant role in providing financing for the development of national fisheries. This study analyzes the factors that influence fisheries financing in Islamic banking in Indonesia and how efforts to increase fisheries sector financing. The processed data source is the monthly statistics of the Islamic banking industry from October 2014 to May 2019, and the method of analysis of this study uses VAR / VECM. The results showed that the NPF and PUAS affect fishery financing in the short term negatively and significantly. Whereas in the long term INF, NPF, PUAS, and ISBIS negatively affect fishery financing, as for CAR, and FDR affects fishery financing positively. Furthermore, SBK, and MRP do not affect fishery financing, both short-term and long-term. This study recommends an increase in the proportion of fishery financing along with an increase in Islamic banking capital, increased monitoring of fishery financing, and strengthening of national monetary policy instruments.Keywords: fisheries financing, Islamic banking, VAR/VECMREFFERENCE Adzimatinur, Fauziyah., Hartoyo, Sri., dan Wiliasih, Ranti. (2015). faktor-faktor yang mempengaruhi besaran pembiayaan perbankan syariah di Indonesia. Jurnal Al-Muzaraah, 3(2), 106-121.Badan Pusat Statistik. Oktober 2014 – Mei 2019, diunduh 12 Agustus 2019, dapat diakses www.bps.go.idBank Indonesia. Oktober 2014 – Meri 2019, diunduh 12 Agustus 2019, dapat diakses www.bi.go.idhttps://kkp.go.id/artikel/2896-bps-nilai-sub-sektor-perikanan-budidaya-mampu-dongkrak-pertumbuhan-ekonomi, jam 10:09 AM. 6/25/2019Ikatan Bankir Indonesia. (2014). Mengelola bisnis pembiayaan bank syariah. Jakarta: Gramedia Pustaka Utama.Gujarati, Damodar N., (2003). Basic econometrics, fourth edition. New York: Gary Burke.Laporan Kinerja KKP. (2016). www.kkp.go.idMuhammad. (2018). Manajemen bank syariah, Yogyakarta: UPP STIM YKPN.Mulyadi. (2007). Ekonomi kelautan. Jakarta: PT Raja Grafindo Persada.Prastanto. (2013). Faktor yang mempengaruhi pembiayaan murabahah pada bank umum syariah di Indonesia,Accounting Analysis Journal, 2(1), 82-88.Rouli Anita Velentina. (2018). Kebijakan pembiyaan bagi nelayan tradisional. Masalah-Masalah Hukum, 47(3), 184-197.Statistik Pembiayaan Syariah, OJK. Oktober 2014 - Mei 2019, diunduh 14 Agustus 2019, dapat diakses www.ojk.go.idStatistik Sistem Keuangan Indonesia, Oktober 2014 – Mei 2019, diunduh 14 Agustus 2019, dapat diakses www.bi.go.idTanjung, Hendri dan Devi, Abrista. (2013). Metodologi penelitian ekonomi Islam. Jakarta: Granata Publishing.Undang-Undang No.45 Tahun 2009. UU Perikanan.Undang-Undang No.31 Tahun 2004 tentang PerikananYozar Putra Jaya, Wiwiek Rindayati, dan Khalifah Muhammad Ali. (2015). Analisis faktor-faktor penentu pembiayaan perbankan syariah pada sektor pengangkutan dan komunikasi di Indonesia. Jurnal Al-Muzara’ah, 3(1), 62-75.Umiyati dan Leni Tantri Ana. (2017). Faktor-Faktor yang mempengaruhi pembiayaan pada bank umum syariah devisa di Indonesia. Jurnal Ekonomi dan Perbankan Syariah, 5(1), 39-61.